2010
DOI: 10.1021/nl101157z
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Cytosolic Delivery of Cell-Impermeable Compounds by Nanoparticle-Mediated, Light-Triggered Endosome Disruption

Abstract: Nanoparticle (NP)-mediated drug delivery typically relies on cargo release to occur passively or in response to environmental stimuli. Here we present a delivery method based on light-activated disruption of intracellular vesicles after internalization of biofunctionalized mesoporous silica nanoparticles loaded with cargo. This method combines the power of targeted delivery with the spatiotemporal control of light activation. As an example, we delivered a cell-impermeable fluorescent compound exclusively to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(82 citation statements)
references
References 37 publications
3
78
0
1
Order By: Relevance
“…178 Also, some hybrid materials that combine photosensitizers and NPs have been described. [179][180][181][182] In all the above examples, PDT is achieved by direct light excitation of photosensitizers, which may be or may not be tagged on passive NPs, cf. Fig.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…178 Also, some hybrid materials that combine photosensitizers and NPs have been described. [179][180][181][182] In all the above examples, PDT is achieved by direct light excitation of photosensitizers, which may be or may not be tagged on passive NPs, cf. Fig.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…This certainly showed that DOX-VRPPENPs successfully reached the nucleus in significant quantities after getting into the cells, to ensure the cytotoxic role of DOX. 46,47 Overall, these results iterate that PENPs co-loaded with VRP have great potential for the delivery of cytotoxic drugs to overcome MDR in tumor treatments. …”
Section: Cellular Uptake Studymentioning
confidence: 68%
“…Febvay et al [88] designed a system based on this strategy, which involved the use of a mesoporous silica nanoparticle to house the drug system, whose surface is decorated with both PEG and antibodies for cell surface targeting. The drug in this case is a model compound, or an Alexa546 membrane impermeable dye to ensure that all fluorescence is attributed to internalized species from the nanoparticle drug delivery system (Fig.…”
Section: Photoresponsive Vesicle Drug Releasementioning
confidence: 99%
“…After nanoparticle endocytosis (b), the cargo is released in the endosome (c). Exposure to light at the dye's excitation wavelength (546 nm) promotes ROS-mediated membrane damage (d) with cytosolic delivery of Alexa546 exclusively in the P-gp expressing cells [88] control over the route of drug delivery and begins to address another critically important question that lies largely unanswered. What can be done to effectively promote the intracellular activity of an internalized drug?…”
Section: Photoresponsive Vesicle Drug Releasementioning
confidence: 99%
See 1 more Smart Citation